PERLINDUNGAN HUKUM TERHADAP KORBAN PELANGGARAN HAK KEKAYAAN INTELEKTUAL - Alfredo Juniotama Arifin; Ruth Elizabeth Marlamb Putri; Tiara Patricia (Keadilan : Jurnal Fakultas Hukum Universitas Tulang Bawang, 2021)
Abstract In running a business, every producer who has a work must be appreciated for his work. The form of appreciation can be done by registering his work to get intellectual property rights so that it can be protected by law. Intellectual Property Rights (IPR) are exclusive rights granted by a law or regulation to a person or group of people for their copyrighted works. In Indonesia IPR has not been implemented properly due to lack of socialization from the government and lack of concern from the community. This encourages the Indonesian government to be more concerned about copyright infringement. Along with the implementation process, it is undeniable that there are still many individuals who do not comply and use a work for commercial purposes. The research method used is the juridical-normative research method. For example, on January 13, 2020, Ruben Samuel Onsu sued I Am Geprek Bensu belonging to PT. Benny Sujono or abbreviated as I Am Geprek Bensu with a trademark abuse lawsuit. There is a need for government supervision of the use of other people's copyrighted works, good coordination between the government and the community so as to minimize the opportunity to commit fraud against a work. Based on the results of the study of cases that occurred, that victims of IPR violations are protected by law based on a first to file system. Â Keywords : Intellectual Property Rights, Legal Protection, Intellectual Property Rights Violation Victims